CROSS-INDUSTRY ANALYSIS OF UKRAINE’S COMPETITIVENESS IN THE WORLD HIGH-TECH GOODS MARKET (INNOVATIVE ECONOMY, 2021)
Marchenko T.V., Tymchuk A.Ya. CROSS-INDUSTRY ANALYSIS OF UKRAINE’S COMPETITIVENESS IN THE WORLD HIGH-TECH GOODS MARKETPurpose. The aim of the article is to study of Ukraine's trade competitiveness in high-tech goods based on data on the value of Ukrainian exports by separate product groups.Methodology of research. The study was based on Ukraine’s international trade data, obtained through queries in the World Integrated Trade Solution web portal, which is a World Bank database. The classification method is used to identify high-tech industries that are relevant to the analysis. The statistical method is used to calculate the relative values of the structure and dynamics of Ukraine's exports. The method of comparative advantages is used to assess the level of competitiveness in different industries. Graphic and tabular methods are used to present the results of the study.Findings. Ukraine's specialization in the production of chemical products, in particular inorganic chemicals, is revealed. Several product groups in the industry of mechanical engineering also possess an advantage, while the results of other, more knowledge-intensive sectors of Ukraine are very far from world standards. The need for state support of knowledge-intensive industries that have the greatest prospects for expanding demand for their products in the future, such as the production of computer equipment and medical instruments and the pharmaceutical industry, is justified.Originality. A quantitative assessment of the level of competitiveness of each industry of Ukraine’s high-tech exports is given. It is demonstrated that among the domestic industries only the production of inorganic chemicals has comparative advantages in the international commodity market, and the degree of lag of all other industries from the world average indicators is calculated.Practical value. The methodology of the analysis, conducted within the framework of this article, can be used by public authorities to monitor the state of competitiveness of Ukrainian industries. Based on the obtained results, operational changes to the state policy of stimulating high-tech industries can be made.Key words: high technologies, high-tech industries, export competitiveness, international trade, comparative advantages, trade in high-tech goods.
Keywords: Key words; high technologies; high-tech industries; export competitiveness; international trade; comparative advantages; trade in high-tech goods.